CONTEXT LEARNING TRANSFORMATION IN ARCHITECTURAL DESIGN STUDIO - Paramita, Kristanti Dewi; Yatmo, Yandi Andri (MODUL, 2020)
This paper reflects the shifting understanding of context in a data-based architectural studio. With the school closure in the beginning of the COVID pandemic, the overall learning process is largely conducted online. Big Data becomes an important discourse that provides some benefits and opportunities which transform the design and learning process in an architectural studio, particularly on how students may explore and understand their context. Exploring the works of third-year architectural students in Department of Architecture, Faculty of Engineering Universitas Indonesia, this paper highlights the ways students capture and organise urban information and construct their intervention contexts. The study points out that time, flow and narrative are key in transforming understanding of context. Based on such three aspects, the data reveals the unseen urban patterns, emerging in the imbalance relationship between user and the environment, the disconnection of urban services, and the hidden variety of urban experience. The study reflects how these urban patterns informs the ways students define and situate themselves in the context, shifting existing ideas of context and its corresponding methodologies in the architectural education.